MACROECONOMIC INFLUENCE AND CREDIT RISK ON SHARIA BANKING ASSET GROWTH IN ASIA - Sasmita, Destina Fitria; Wicaksono, Ahmad Tibrizi Soni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The aim of this research is to identify the effect of macroeconomic and credit risk on the growth of Islamic banking assets in Asia.This study uses a type of quantitative research. The population of this study are countries that have Islamic banks and are included in the Asian region of 48 countries. By using a purposive sampling technique, the number of samples in this study were 16 countries. The data analysis technique is panel data regression using EViews 12.0 software. The results of this study indicate that partially the macroeconomic proxies for inflation, GDP, and the unemployment rate have a significant effect on the growth of Islamic banking assets in Asia. In addition, credit risk proxied by NPF has no effect on the growth of Islamic banking assets in Asia. As for simultaneously the variables of inflation, GDP, and the unemployment rate affect the growth of Islamic banking assets in Asia